EVALUASI FAKTOR-FAKTOR PENTING PENYEBAB PENAMBAHAN BIAYA PROYEK JALAN APBD KABUPATEN SRAGEN TAHUN 2017 DAN 2018 - Muhammad Nur Sahid; Anto Budi L; Abdul Rochman; Devi Cahyaningtyas (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2019)
The development of a country can be known by the expansion of its transportation facilities. Looking at the importance of roads for a region, there are many improvements and additions to these facilities and infrastructure. In the process of repairing the roads, some risks could be possibly causing failures such as time delay and cost overrun. The purpose of this study is to determine the important and the dominant factors that lead to the overrun cost to the road projects in Sragen Regency in 2017 and 2018. The data were obtained by distributing the questionnaires to the contractors who had handled the road projects in Sragen Regency. The results of the questionnaires survey collected 98 questionnaires of 55 contractors. The data analysis is using the program SPSS (Statistical Package for Social Science) Ver 25.0. The results of this study are the factors that cause overrun cost to the road projects in Sragen Regency in 2017 and 2018, are the implementation and the relationship of work and equipment, and the dominant factors that cause overrun cost to road projects in Sragen Regency in 2017 and 2018 is the implementation and the relationship of work.